Metal bismuth-based solid solution alloy material as well as preparation method and application thereof
By introducing non-metal atoms into metal bismuth-based solid solution alloy materials to form high-strength Bi-O bonds, the problem of poor activity and selectivity of electrocatalytic carbon dioxide reduction technology under alkaline conditions is solved, and efficient catalysis and stability are achieved, combined with waste Plastics degrade co-production of formic acid, improving energy utilization efficiency and economic benefits.
Patent Information
- Application Number
- CN202411607151.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing electrocatalytic carbon dioxide reduction technology has problems such as poor catalytic activity and selectivity, large energy consumption, low product selectivity and insufficient catalyst stability under alkaline conditions. Especially when using Bi-based catalysts, the activity is not satisfactory and the preparation process is High energy consumption.
By introducing non-metallic atoms such as P, B, S or N into metal bismuth-based solid solution alloy materials, high-strength Bi-O bonds are formed, the surface chemical potential of metal Bi is changed, its oxygen availability is improved, and solvent-thermal reaction is used Methods to prepare the material in one step, simplify the process and reduce costs.
It has achieved efficient catalytic carbon dioxide reduction under neutral or alkaline conditions, significantly improved the Faraday efficiency and stability of formic acid, reduced energy consumption, and degraded co-generated formic acid with waste plastics under solar power, improving economic benefits.
Smart Images

Figure CN119144871A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid solution alloy materials, and in particular to a metal bismuth-based solid solution alloy material and a preparation method and application thereof. Background Art
[0002] How to deal with excess carbon dioxide has become a topic of widespread concern. Existing treatment methods include thermal catalysis, photocatalysis and biocatalysis, but these treatment methods have huge usage costs and energy consumption. However, electrocatalysis is widely used in CO2 treatment due to its mild reaction conditions, simple operation and environmental friendliness. 2 In addition, electrocatalytic CO 2 As a typical half-reaction, reduction reaction participates in many energy catalysis and conversion processes. In recent years, a lot of research has been conducted on the treatment and resource utilization of waste plastics. Reports show that the use of electrocatalytic technology can selectively oxidize ethylene glycol in PET hydrolysis products into formate and produce hydrogen at the cathode. 2 The introduction of the reduction half-reaction into the plastic degradation and upgrading system can, on the one hand, reduce the initial potential of plastic oxidation and increase its reactivity; on the other hand, it can convert CO 2 Combining RR with anodic plastic oxidation upgrading to formic acid to generate similar reaction products has the economic advantages of improving energy utilization efficiency and expanding the conversion system to a certain extent.
[0003] However, there are still many challenges in electrocatalytic CO2 reduction technology, such as 2 The molecule has high thermodynamic stability, and the activation of C=O requires overcoming a high energy barrier. 2 Low solubility and the presence of hydrogen evolution reaction (HER) lead to problems such as poor product selectivity, low current density, and insufficient stability during the reaction. Especially under alkaline conditions, CO 2 The direct formation of carbonates or bicarbonates with the electrolyte results in a low gas conversion rate, and the carbonates formed easily block the pores of the catalyst. For various reasons, the electrocatalytic reduction of CO under alkaline conditions 2 The process consumes a lot of energy and lacks economic benefits. Therefore, it is very important to find a catalyst that has high catalytic activity and selectivity under alkaline conditions and is economical and practical.
[0004] Bi-based catalysts have attracted much attention due to their low toxicity, low cost, and high hydrogen evolution reaction (HER) potential. 2 Reduction reaction (ECO 2The activity of RR is not very satisfactory, so it is very necessary to develop and prepare cheap and efficient Bi-based catalysts for carbon dioxide reduction. In addition, in previous studies, the process of introducing non-metallic elements into Bi-based materials is divided into two steps: precursor preparation and post-doping, which not only consumes energy, but also the high temperature involved in post-doping may cause uncontrollable collapse of the structure. Therefore, it is of great significance to study and develop a new type of catalyst with high catalytic activity and stability for electrocatalytic carbon dioxide reduction. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a metal bismuth-based solid solution alloy material and a preparation method and application thereof. The metal bismuth-based solid solution alloy material has excellent catalytic activity and good stability in electrocatalytic carbon dioxide reduction.
[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] The present invention provides a metal bismuth-based solid solution alloy material, comprising metal bismuth and non-metallic atoms doped therein;
[0008] The non-metal atom is selected from P, B, S or N.
[0009] The metal bismuth-based solid solution alloy material contains high-strength Bi-O bonds.
[0010] The present invention changes the surface chemical potential of metal Bi by doping with non-metal atoms, thereby enhancing the oxygen affinity of metal Bi, wherein the oxygen comes from dissolved oxygen in the air or solvent. The non-metal atoms are dissolved in the lattice of metal Bi in a solid form to form a metal Bi-based solid solution alloy material.
[0011] The metal bismuth-based solid solution alloy material is represented by P-Bi, B-Bi, S-Bi or N-Bi.
[0012] The present invention obtains the above-mentioned solid solution alloy by introducing non-metallic atoms into the metal bismuth-based lattice. Due to the introduction of non-metallic atoms, the surface of the material is highly oxidized, thereby containing high-strength Bi-O bonds, which regulates the crystal plane changes of the metal bismuth base during the reaction process, and through the doping of non-metallic atoms, the activity of electrocatalytic carbon dioxide reduction is effectively improved.
[0013] In the present invention, the ratio of the Bi-O bond strength in the metal bismuth-based solid solution alloy material P-Bi to the Bi-O bond strength in Bi (Bipowder or Bi reference obtained in Comparative Example 1) is nearly 3 times.
[0014] Preferably, in the present invention, the doping amount of the non-metallic atoms is 0.1 wt%-3.1 wt%; more preferably, 2.0 wt%-3.0 wt%; further preferably, 2.5 wt%-3.0 wt%; and further preferably, 2.9 wt%.
[0015] Preferably, in the present invention, the morphology of the metal bismuth-based solid solution alloy material is irregular nanosheets.
[0016] The non-metal atoms and metal bismuth in the above-mentioned metal bismuth-based solid solution alloy material P-Bi, B-Bi, S-Bi or N-Bi are uniformly distributed.
[0017] The present invention also provides a method for preparing the above-mentioned metal bismuth-based solid solution alloy material, comprising the following steps:
[0018] The bismuth metal salt, the non-metallic source compound and the solvent are mixed to prepare the metal bismuth-based solid solution alloy material through a solvothermal reaction;
[0019] The bismuth metal salt includes but is not limited to bismuth nitrate pentahydrate, bismuth chloride and the like.
[0020] The non-metal source compound is selected from compounds containing P, B, S or N.
[0021] The above-mentioned preparation method realizes the preparation of metal bismuth-based solid solution alloy materials through a "one-pot method". The material is prepared in one step through a solvent thermal in-situ reduction method, without the need to first prepare a metal bismuth-based precursor and then dope non-metallic atoms. The preparation method is simple and efficient, saves time and cost, and is suitable for large-scale industrial production.
[0022] Furthermore, the required temperature of the preparation method of the present invention is relatively low, so that the structure of the metal bismuth-based solid solution alloy material is stable and thus the catalytic performance is stable.
[0023] Preferably, the temperature of the solvothermal reaction is 160°C-200°C, more preferably 170°C-190°C. In some specific embodiments of the present invention, it is preferably 180°C.
[0024] The heating time is preferably 10-30 h; more preferably 15-25 h; in some specific embodiments of the present invention, preferably 24 h.
[0025] Preferably, in the present invention, the molar ratio of the bismuth metal salt to the non-metal source compound is (10-20):1; more preferably (12-18):1; further preferably 50:3.
[0026] Preferably, the non-metallic source compound is selected from NaH 2 PO 2 ·H2 O, H 3 BO 3 , C 2 H 5 NS or CO(NH 2 ) 2 .
[0027] Preferably, the solvent is selected from N,N-dimethylformamide.
[0028] The above preparation method further comprises post-treatment of washing and drying after the solvent thermal reaction is completed.
[0029] The present invention has no particular limitation on the washing solvent and drying method, and any solvent or method well known to those skilled in the art may be used.
[0030] In some specific embodiments of the present invention, the washing solvent is preferably deionized water and anhydrous ethanol.
[0031] In some specific embodiments of the present invention, the drying is preferably freeze-drying under vacuum conditions.
[0032] The present invention has no particular limitation on the container for the solvent thermal reaction, and in the present invention, a polytetrafluoroethylene reactor is preferred.
[0033] The present invention also provides the use of the above-mentioned metal bismuth-based solid solution alloy material or the metal bismuth-based solid solution alloy material prepared by the above-mentioned preparation method as a catalyst in electrocatalytic carbon dioxide reduction.
[0034] In the present invention, preferably, the electrocatalytic carbon dioxide reduction reaction is carried out under neutral or alkaline conditions to achieve a higher formic acid Faradaic efficiency.
[0035] Furthermore, the bismuth-based solid solution alloy material of the present invention is effective in electrocatalytic CO 2 It has excellent stability and outstanding formic acid Faradaic efficiency during reduction.
[0036] The present invention also provides the use of the above-mentioned metal bismuth-based solid solution alloy material or the metal bismuth-based solid solution alloy material prepared by the above-mentioned preparation method as a cathode catalyst in electrocatalytic carbon dioxide reduction coupled with anode waste plastic degradation to produce formic acid.
[0037] The electrocatalytic carbon dioxide reduction coupled with anode waste plastic degradation to produce formic acid is carried out by coupling a cathode electrocatalytic carbon dioxide reduction reaction with an anode waste plastic hydrolysis product oxidation reaction.
[0038] The metal bismuth-based solid solution alloy material is used as a cathode catalyst to electrocatalyze carbon dioxide reduction under neutral or alkaline conditions. The above coupling is carried out under the drive of solar energy, which is environmentally friendly, safe and low-cost.
[0039] In the present invention, the above-mentioned material is used as a catalyst for electrocatalytic carbon dioxide reduction, coupling the carbon dioxide reduction reaction at the cathode and the oxidation reaction of the PET hydrolysis product at the anode, so that formic acid is generated at the cathode and the anode at the same time, thereby significantly improving the formic acid yield. 2 The RR / / PET ER coupling system can increase revenue by more than $200 / ton PET compared to HER / / PET ER.
[0040] Compared with the prior art, the metal bismuth-based solid solution alloy material provided by the present invention includes metal bismuth and non-metallic atoms doped therein; the non-metallic atoms are selected from P, B, S or N. The present invention obtains a solid solution alloy by introducing non-metallic atoms into the metal bismuth-based lattice, so that a high-strength Bi-O bond is formed on the surface of the metal bismuth-based solid solution alloy material, thereby regulating the crystal plane change during the reaction process, and through the doping of non-metallic atoms, the activity of electrocatalytic carbon dioxide reduction is effectively improved, so that the metal bismuth-based solid solution alloy material has excellent formic acid Faraday efficiency and good stability when used as a catalyst to electrocatalytically reduce carbon dioxide to produce formic acid. In addition, the metal bismuth-based solid solution alloy material, as a catalyst, couples the electrocatalytic carbon dioxide reduction reaction of the cathode and the oxidation reaction of the PET hydrolysis product of the anode to achieve the degradation of waste plastics and the generation of high-yield formic acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 X-ray diffraction patterns (XRD patterns) of the solid solution alloy materials obtained in Examples 1 to 4 and the material Bi obtained in Comparative Example 1, wherein Bi (PDF#05-0519) is a standard diffraction card of Bi;
[0042] Figure 2 This is a scanning electron microscope image (SEM image) of the solid solution alloy material P-Bi obtained in Example 1;
[0043] Figure 3 This is a transmission electron microscope image (TEM image) of the solid solution alloy material P-Bi obtained in Example 1;
[0044] Figure 4 This is the transmission electron microscope EDS mapping image of the solid solution alloy material P-Bi obtained in Example 1;
[0045] Figure 5 Figure a shows the L of Bi in the solid solution alloy material P-Bi obtained in Example 1 3-edge X-ray absorption extension edge in R space, b is a comparison of Bi-O bond strength in Bi powder, Bi obtained in comparative example 1 (Bi reference) and P-Bi solid solution alloy material obtained in example 1;
[0046] Figure 6 This is a graph of the carbon dioxide reduction performance of the solid solution alloy material P-Bi obtained in Example 1 under neutral conditions;
[0047] Figure 7 This is a graph showing the carbon dioxide reduction performance of the solid solution alloy material P-Bi obtained in Example 1 under alkaline conditions;
[0048] Figure 8 The solid solution alloy material P-Bi obtained in Example 1 was electrocatalyzed in a flow cell to produce CO 2 Stability test of reduction and Faradaic efficiency diagram of formic acid production;
[0049] Fig. 9 The solid solution alloy material P-Bi obtained in Example 1 is driven by solar energy and the cathode CO 2 RR coupling anode waste plastic reforming experiment demonstration diagram;
[0050] Fig.10 This is a diagram of the terephthalic acid product obtained from the solid solution alloy material P-Bi obtained in Example 1 after reforming waste plastics;
[0051] Fig.11 The solid solution alloy material P-Bi obtained in Example 1 is driven by solar energy to form a cathode CO 2 RR (Fig. b) and coupled anodic waste plastic degradation and upgrading to produce formic acid (Fig. a) 1 H NMR spectrum;
[0052] Fig.12 This is a comparison chart of the Faraday efficiency of the P-Bi obtained in Example 1 and the material Bi obtained in Comparative Example 1 in the electrocatalytic carbon dioxide reduction reaction under alkaline conditions;
[0053] Fig.13 This is a comparison chart of the current density of the electrocatalytic carbon dioxide reduction reaction of P-Bi obtained in Example 1 and the material Bi obtained in Comparative Example 1 under alkaline conditions;
[0054] Fig.14 The linear sweep voltammetry curves of the Bi materials obtained in Examples 1 to 4 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0055] In order to further illustrate the present invention, the metal bismuth-based solid solution alloy material provided by the present invention and its preparation method and application are described in detail below in conjunction with embodiments.
[0056] 1. Preparation of Materials
[0057] Example 1
[0058] Preparation of P-Bi catalyst
[0059] 2mmol of bismuth nitrate pentahydrate and 120μmol of sodium hypophosphite were weighed and dissolved in 12mL of dimethylformamide, and a uniform mixed solution was formed after 20min of ultrasonic dissolution. The above solution was then transferred to a 50mL polytetrafluoroethylene reactor and reacted at 180°C for 24 hours. After the reaction was completed, it was cooled to room temperature, and the obtained product was fully washed with water and anhydrous ethanol, respectively, and then lyophilized under vacuum conditions for 24 hours to obtain a solid solution alloy material P-Bi.
[0060] Example 2
[0061] The method is implemented in accordance with Example 1, except that sodium hypophosphite is replaced by boric acid to obtain material B-Bi.
[0062] Example 3
[0063] The process was carried out in accordance with Example 1, except that sodium hypophosphite was replaced with thioacetamide to obtain material S-Bi.
[0064] Example 4
[0065] The method is implemented in accordance with Example 1, except that sodium hypophosphite is replaced by urea to obtain material N-Bi.
[0066] Comparative Example 1
[0067] Weigh 2mmol of bismuth nitrate pentahydrate and dissolve it in 12mL of dimethylformamide. After 20min of ultrasonic dissolution, a uniform mixed solution is formed. Then the above solution is transferred to a 50mL polytetrafluoroethylene reactor and reacted at 180°C for 24 hours. After the reaction is completed, cool to room temperature, wash the obtained product with deionized water and anhydrous ethanol, respectively, and then freeze-dry under vacuum conditions for 24 hours to obtain material Bi.
[0068] 2. Material structure characterization and performance testing
[0069] (1) Characterization:
[0070] Figure 1 X-ray diffraction patterns (XRD) of the solid solution alloy materials P-Bi, B-Bi, S-Bi, N-Bi obtained in Examples 1-4, and the material Bi obtained in Comparative Example 1, respectively. XRD confirms that the physical phases of the above solid solution alloy materials are all Bi, and there are no phases related to P, B, S, and N, indicating that P, B, S, and N are all present in the solid solution alloy material in an atomically dispersed form.
[0071] Figure 2 This is a scanning electron microscope (SEM) image of the solid solution alloy material P-Bi obtained in Example 1. SEM shows that the morphology of P-Bi is irregular nanosheets.
[0072] Figure 3 This is the transmission electron microscope (TEM) image of the solid solution alloy material P-Bi obtained in Example 1. Obvious lattice fringes can be observed, corresponding to the Bi (012) crystal plane.
[0073] Figure 4 This is the transmission electron microscope (EDS) mapping image of the solid solution alloy material P-Bi obtained in Example 1. The results show that the Bi and P elements are evenly distributed on the surface of the material.
[0074] Figure 5 The L of Bi in the solid solution alloy materials obtained in Examples 1-4, the Bi material obtained in Comparative Example 1 (shown in the Bi reference curve), and the Bi powder (shown in the Bi powder curve, the powder Bi was purchased from Sinopharm Group or Aladdin Reagent Co., Ltd.) 3 -edge X-ray absorption extension edge display diagram in R space. The results show that in the above-mentioned solid solution alloy material, the introduction of P in the P-Bi material makes the P-Bi surface highly oxidized and the Bi-O intensity is the largest.
[0075] (2) Electrocatalytic carbon dioxide reduction test of solid solution alloy material P-Bi: 4 mg of solid solution alloy material P-Bi (prepared in Example 1) was weighed and dispersed in a mixed solution (mixed solution = 500 μL water + 460 μL ethanol + 40 μL 0.5% perfluorosulfonic acid type polymer solution (Nafion aqueous solution)), and ultrasonically dispersed for 1 hour. After the dispersion was uniform, 160 μL of the obtained suspension was transferred with a pipette and dropped on an area of 1 cm 2 On carbon paper, dried at room temperature, as the working electrode. In addition, a standard three-electrode system was constructed with an Ag / AgCl electrode calibrated with a standard hydrogen electrode as the reference electrode and a platinum wire as the counter electrode.
[0076] Neutral conditions test: Using the above three-electrode system, a 0.5 M KHCO 3 The electrochemical performance of the H-type electrolytic cell of the solution was tested on a Shanghai Chenhua electrochemical workstation (CHI 760E). 2 The gas was pre-bubbled for 20 min to saturate the solution, and the constant gas flow rate was 20 mL / min. Constant potential electrolysis was performed for 1 hour at -0.7 V to -1.2 V vs. RHE potentials. The gas after the electrolysis reaction was detected by online gas chromatography, and the liquid product was detected by nuclear magnetic resonance spectroscopy ( 1HNMR) detection.
[0077] Test results such as Figure 6 As shown, Figure 6 This is a graph of the carbon dioxide reduction performance of the solid solution alloy material P-Bi obtained in Example 1 under neutral conditions. It can be seen that the Faraday efficiency of formic acid can still be maintained at more than 90% in the voltage range of -0.9 V to -1.1 V vs. RHE, wherein the Faraday efficiency of formic acid at a voltage of -1.1 V vs. RHE is 95.2%.
[0078] Alkaline condition test: The solid solution alloy material P-Bi prepared in Example 1 was used to prepare ink, which was dripped on an area of 1 cm 2 In addition, a Ag / AgCl electrode calibrated with a standard hydrogen electrode was used as the reference electrode, and nickel foam (1.5 cm × 1.5 cm, with an effective area of 1 cm 2 ) was used as the counter electrode. A peristaltic pump was used to flow 1.0 M KOH electrolyte in the flow cell, and the electrochemical performance test was performed on a Shanghai Chenhua electrochemical workstation (CHI 760E). During the test, CO 2 The gas was continuously introduced at a constant flow rate of 20 mL / min.
[0079] Test results such as Figure 7 As shown, Figure 7 This is a graph of the carbon dioxide reduction performance of the solid solution alloy material P-Bi obtained in Example 1 under alkaline conditions. It can be seen that P-Bi has achieved a formic acid Faraday efficiency of 94.3% at -1.0 V vs. RHE.
[0080] Figure 8 The solid solution alloy material P-Bi obtained in Example 1 was electrocatalyzed in a flow cell to produce CO 2 The stability test of reduction and the Faraday efficiency diagram of formic acid production. It can be concluded that the current density of P-Bi can reach more than 300 mA / cm at -1.0V vs. RHE. 2 , and sustained stable electrolysis for nearly 20 hours, which has strong potential for industrial application.
[0081] (3) Cathode CO driven by solar energy 2 RR (cathode catalyst is solid solution alloy material P-Bi) coupled anode for waste plastic degradation experiment
[0082] Anode electrode preparation: prepare 200mL 0.05mol / L Ni(NO 3 ) 2 6H 2 O+0.05mol / L Co(NO3 ) 2 6H 2 O-containing electrodeposition solution, with nickel foam as the working electrode and counter electrode, and Ag / AgCl as the reference electrode, the CoNi-LDH / NF electrode was obtained by electrodeposition at -1.2 V vs. SHE for 3600 s.
[0083] The material P-Bi prepared in Example 1 was used to prepare ink (an ink-like slurry formed by a catalyst and a solvent under ultrasonic conditions) and then dripped onto an area of 1 cm 2 The carbon paper is used as the cathode carbon dioxide reduction catalytic electrode, and the CoNi-LDH / NF electrode prepared above is the anode electrode for degrading plastics. The electrolytic cell is assembled and the reaction is carried out under the drive of the solar cell, such as Fig. 9 The cathode CO is driven by solar energy. 2 RR coupled anode for waste plastic reforming experiment demonstration diagram. After the reaction is completed, the electrolyte of the anode is collected, and the liquid product is analyzed by nuclear magnetic resonance spectroscopy ( 1 H NMR) detection, and then adjust the pH to separate the product terephthalic acid, such as Fig.10 Shown is a diagram of the terephthalic acid product obtained after reforming waste plastics. Fig.11 Solar-powered cathode CO 2 RR and coupled anodic degradation and upgrading of waste plastics to produce formic acid 1 H NMR spectrum shows that after the reaction, the liquid products at the cathode and anode are both formic acid.
[0084] (4) Electrocatalytic CO2 Reduction of Material Bi Prepared in Comparative Example 1
[0085] According to the electrocatalytic performance testing method of the material in Example 1, the catalytic performance test of the material Bi prepared in Comparative Example 1 was carried out under the same alkaline conditions.
[0086] The test results are as follows Fig.12 and Fig.13 As shown, Fig.12 The figure is a comparison of the Faraday efficiency of the P-Bi obtained in Example 1 and the Bi material obtained in Comparative Example 1 in the electrocatalytic carbon dioxide reduction reaction under alkaline conditions. Fig.13 This is a comparison of the current density of the electrocatalytic carbon dioxide reduction reaction under alkaline conditions. Fig.12 and Fig.13 The results show that the formic acid Faraday efficiency and current density of the material Bi in comparative example 1 are much lower than those in example P-Bi, indicating that non-metallic doping can significantly improve the catalytic activity of the material.
[0087] (5) Electrochemical performance test of the materials obtained in Examples 1-4 and Comparative Example 1
[0088] The electrocatalysts prepared in Examples 1 to 4 and Comparative Example 1 were placed in CO 2 Saturated 0.5M KHCO 3 The electrochemical performance was tested using an electrochemical workstation (CHI760E) to obtain a linear sweep voltammetric curve, as shown in Fig.14 shown.
[0089] The results show that the electrochemical properties of the materials prepared in Examples 1-4 of the present invention are better than those in Comparative Example 1. However, compared with Examples 2-4, the performance of the material in Example 1 of the present invention is the best.
[0090] In summary, the solvothermal method used in the present invention can be used to simply and conveniently prepare metal bismuth-based solid solution alloy materials, and the catalytic performance of the materials is excellent. The present invention obtains Y-Bi solid solution alloy materials doped with different heteroatoms by regulating non-metallic source compounds. Taking P-Bi as an example, by introducing heteroatoms to form high-strength Bi-O on the surface of the material, the crystal plane changes during the reaction are regulated. Under neutral conditions, over a wide voltage range, the formic acid Faraday efficiency is always maintained at more than 90%; under alkaline conditions, P-Bi can still maintain more than 90% formic acid selectivity, and the current density can exceed 300mA / cm 2 At this current, it can run stably for nearly 20 hours, effectively improving the electrocatalytic carbon dioxide activity. At the same time, driven by solar energy, the material described in the present invention can be coupled with the anode's waste plastic degradation and recovery to produce formic acid.
[0091] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A metal bismuth-based solid solution alloy material, characterized in that: It includes metallic bismuth and non-metallic atoms doped therein; The non-metal atom is selected from P, B, S or N.
2. The metal bismuth-based solid solution alloy material according to claim 1, characterized in that: The doping amount of the non-metal atoms is 0.1 wt%-3.1 wt%.
3. The metal bismuth-based solid solution alloy material according to claim 1, characterized in that: The morphology of the metal bismuth-based solid solution alloy material is irregular nanosheets.
4. The method for preparing the metal bismuth-based solid solution alloy material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The bismuth metal salt, the non-metallic source compound and the solvent are mixed to prepare the metal bismuth-based solid solution alloy material through a solvothermal reaction; The non-metal source compound is selected from compounds containing P, B, S or N.
5. The preparation method according to claim 4, characterized in that: The temperature of the solvent thermal reaction is 160°C-200°C.
6. The preparation method according to claim 4, characterized in that: The molar ratio of the bismuth metal salt to the non-metal source compound is (10-20):
1.
7. The preparation method according to claim 4, characterized in that: The non-metal source compound is selected from NaH2PO2·H2O, H3BO3, C2H5NS or CO(NH2)2.
8. The preparation method according to claim 4, characterized in that: The solvent is selected from N,N-dimethylformamide.
9. Use of the metal bismuth-based solid solution alloy material according to any one of claims 1 to 3 or the metal bismuth-based solid solution alloy material prepared by the preparation method according to any one of claims 4 to 8 as a catalyst in electrocatalytic carbon dioxide reduction.
10. Use of the bismuth-based solid solution alloy material according to any one of claims 1 to 3 or the bismuth-based solid solution alloy material prepared by the preparation method according to any one of claims 4 to 8 as a cathode catalyst in electrocatalytic carbon dioxide reduction coupled with anode waste plastic degradation to produce formic acid; The electrocatalytic carbon dioxide reduction coupled with anode waste plastic degradation to produce formic acid is carried out by coupling a cathode electrocatalytic carbon dioxide reduction reaction with an anode waste plastic hydrolysis product oxidation reaction; The metal bismuth-based solid solution alloy material is used as a cathode catalyst to perform electrocatalytic carbon dioxide reduction under neutral or alkaline conditions.
Citation Information
Patent Citations
Bismuth series photocatalyst, and preparation method thereof
CN102600829A
Catalyst for preparing formic acid from carbon dioxide by electroreduction and preparation method of catalyst
CN109675586A
Photocathode material for preparing formic acid by reducing CO2 and preparation method thereof
CN113308702A
Nonmetal doped bismuth layered oxide and preparation method and application thereof
CN118026259A
Preparation method of electrode material for converting carbon dioxide into formic acid through electrocatalytic reduction
CN118581484A
